Perception of ‘Peace’ From A Religious Perspective: A Metaphorical Analysis of Martin Luther King Jr.’s Nobel Prize Speech: Aliakbar Imani: Language Academy, Universiti Technologi Malaysia - Aliakbar Imani (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2022)
Abstract: Rev. Dr. Martin Luther King Jr.’s eloquence as an orator is widely recognized all over the world and his rhetorical strategies have been subject to many studies. However, very few studies have looked into his use of metaphor as an effective cognitive device and communication strategy. Hence, this paper, drawing upon Lakoff and Johnson’s (1980) Conceptual Metaphor Theory, provides a metaphorical analysis of his Nobel Prize acceptance speech (1964), which is among his most popular and influential speeches in the history, to understand the way ‘peace’ is perceived by him and conveyed to the audience. The findings of this study reveal that this speech is highly metaphorical, which seems to be one of the reasons of its popularity and effectiveness. The findings of the study also reveal that, while King is considered both as a political and religious leader, ‘peace’ is dominantly framed from a religious perspective via metaphors of ‘light’ and ‘journey’, positioning him as a religious rather than political leader. Furthermore, it is argued that the use of dualistic image-making as one of his discursive strategies makes his metaphors more impactful. For instance, while Peace is portrayed as Light, lack of Peace is portrayed as Darkness; and while Peace is portrayed as an Upward Movement, lack of Peace is portrayed as a Downward Movement. Finally, accompanying metaphorical words with adjectives (for instance, employing adjectives of ‘dark’, ‘starless’, and ‘long’ for the metaphorical ‘night’) gives a more emphatic tone to his metaphors.     Keywords: Martin Luther King Jr.; Metaphor Analysis; Nobel Peace Prize; Peace; Religious discourse.